Expansion of human mesenchymal stem cells in a fixed-bed bioreactor system based on non-porous glass carrier – Part B: Modeling and scale-up of the system - Weber, Christian; Freimark, Denise; Portner, Ralf; Pino-Grace, Pablo; Pohl, Sebastian; Wallrapp, Christine; Geigle, Peter; Czermak, Peter (Wichtig Editore, 2018)
Human mesenchymal stem cells (hMSC) are a promising cell source for the manufacturing of cell therapeutic or tissue engineered implants. In part A of this publication a fixed-bed bioreactor system based on non-porous borosilicate glass spheres and procedures for the automated expansion of hMSC with high yield and vitality has been introduced. Part B of this study deals with the modeling of the process in order to transfer the bioreactors system from the laboratory to the production scale. Relevant model parameters have been obtained by fitting them to the experimental data of hMSC-TERT cultivations in scales up to 300 cm3. Scale-up calculations were carried out exemplarily for a target cell number of twenty billion cells.
Keywords: Mesenchymal stem cells; hMSC-TERT; Fixed-bed bioreactor; Glass carrier; Scale up